Intruder capture algorithms considering visible intruders. (8th May 2019) - Kim, Jonghoek
In this article, we consider the problem of using multiple robots (searchers) to capture intruders in an environment. Assume that a robot can access the position of an intruder in real time, that is, an intruder is visible by a robot. We simplify the environment so that robots and worst-case intruders move along a weighted graph, which is a topological map of the environment. In such settings, a worst-case intruder is characterized by unbounded speed, complete awareness of searcher location and intent, and full knowledge of the search environment. The weight of an edge or a vertex in a weighted graph is a cost describing the clearing requirement of the edge or the vertex. This article provides non-monotone search algorithms to capture every visible intruder. Our algorithms are easy to implement, thus are suitable for practical robot applications. Based on the non-monotone search algorithms, we derive the minimum number of robots required to clear a weighted tree graph. Considering a general weighted graph, we derive bounds for the number of robots required. Finally, we present switching algorithms to improve the time efficiency of capturing intruders while not increasing the number of robots. We verify the effectiveness of our approach using MATLAB simulations.